Refractory Lactic Acidosis in Small Cell Carcinoma of the Lung - Daniel J. Oh; Ellen Dinerman; Andrew H. Matthews; Abraham W. Aron; Katherine M. Berg (Case Reports in Critical Care)
Background. Elevated lactate levels in critically ill patients are most often thought to be indicative of relative tissue hypoxia or type A lactic acidosis. Shock, severe anemia, and thromboembolic events can all cause elevated lactate due to tissue hypoperfusion, as well as the mitochondrial dysfunction thought to occur in sepsis and other critically ill states. Malignancy can also lead to elevation in lactate, a phenomenon described as type B lactic acidosis, which is much less commonly encountered in the critically ill. Case Presentation. We present the case of a 73-year-old Caucasian woman with type 2 diabetes and hypertension who presented with abdominal pain, nausea, vomiting, nonbloody diarrhea, and weight loss over five weeks and was found to have unexplained refractory lactic acidosis despite fluids and antibiotics. She was later diagnosed with small cell carcinoma of the lung. Conclusions. In this case report, we describe a critically ill patient whose elevated lactate was incorrectly attributed to her acute illness, when in truth it was an indicator of an underlying, as yet undiagnosed, malignancy. We believe this case is instructive to the critical care clinician as a reminder of the importance of considering malignancy on the differential diagnosis of a patient presenting with elevated lactate out of proportion to their critical illness.